PENERAPAN MODEL PROBLEM BASED LEARNING UNTUK MENINGKATKAN HASIL BELAJAR MATEMATIKA SISWA KELAS VII3 SMP NEGERI 4 PEKANBARU - Helmawati; Yurhagusfiani; Rini Dian Anggraini (Jurnal Prinsip Pendidikan Matematika, 2019)
This research aimed to improve the learning process and improved the student’s mathematic achievement through the implementation of problem based learning. The research was the classroom action research with two cycles. The research was conducted in student of class VII3 SMPN 4 Pekanbaru in odd semester of the 2018/2019 academic year with the subject is 38 students. The research instruments consist of learning devices and data collector instrument. Learning devices consists of the syllabus, lesson plan and student worksheet. The data collector instrument consists of the observation sheet and mathematics test. Technique of data analysis is analysis of narrative descriptive and analysis of statistical descriptive. The result of the research show that the learning process has improved and the student’s mathematic achievement has improved after applying the problem based learning model. The percentage of student who achieve minimal completeness criteria on first cycle was 68,42% and the second cycle was 78,94% which greater than the percentage of student who achieve minimal completeness criteria before implementation of problem based learning that only 44,73%. Therefore, the problem based learning can be used as an alternative in learning.